Cultural exchanges and current research in Kültepe and its surroundings (Turnhout, Belgium)
xvi, 332 sayfa
Keywords: “This fourth volume of the Kültepe International Meetings (KIM) gathers archaeological, historical and philological studies dedicated to Kültepe, ancient Kaneš (central Anatolia) and its surroundings.” --